2020
DOI: 10.1016/j.etap.2020.103409
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of diuron metabolites in human cells

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…Dentre os herbicidas mais utilizados ao redor do mundo pode-se citar o diuron, sendo também um dos mais eficazes no que diz respeito ao controle de ervas daninhas indesejadas (LIU et al, 2018;MOHAMMED;HUOVINEN;VÄHÄKANGAS, 2020).…”
Section: O Herbicida Diuronunclassified
“…Dentre os herbicidas mais utilizados ao redor do mundo pode-se citar o diuron, sendo também um dos mais eficazes no que diz respeito ao controle de ervas daninhas indesejadas (LIU et al, 2018;MOHAMMED;HUOVINEN;VÄHÄKANGAS, 2020).…”
Section: O Herbicida Diuronunclassified
“…This suggests that pregnant women can suffer fetotoxicity if they are exposed to DUR. Mohammed et al (2020) indicated that DUR metabolites are more toxic than the parent compound in human cells, with the mitochondria as their target. Concerning the effects of chronic exposure to herbicides and the mechanisms involved, several questions regarding ecotoxicology remain to be addressed ( Akcha et al, 2020 ).…”
Section: Environmental Occurrence and Toxicitymentioning
confidence: 99%
“…Generally, chemical metabolism in plants typically occurs in four distinct ways, including Phase I (simple functional group changes), Phase II (conjugation with plant endogenous compounds), Phase III (transportation), and noncanonical Phase IV (other reactions) . Few DU derivatives have been currently identified in microbes, aquatic life, weed plants, animals, and human cells, such as 3,4-dichloroanilines, N -3,4-dichlorophenylurea, and N -(3,4-dichlorophenyl)- N -methylurea, which belong to the Phase I metabolites and have been proved to be a higher risk for human beings than the parent compound due to the increasing evidence of their genotoxic and teratogenic properties in animals. , The Phase II metabolic process is considered an important detoxification approach for most toxins, where lower toxic metabolites are generated by the binding with hydrophilic endogenous like sugar, amino acid, sulfate, or phosphate groups. These Phase II-based metabolites could be easily excreted from plant cells or transferred to vacuoles for isolation by transporters in the Phase III process .…”
Section: Introductionmentioning
confidence: 99%